2018
DOI: 10.1088/1674-1056/27/3/037102
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigations of proton generation in α -quartz

Abstract: Proton plays a key role in the interface-trap formation that is one of the primary reliability concerns, thus learning how it behaves is key to understand the radiation response of microelectronic devices. The first-principles calculations have been applied to explore the defects and their reactions associated with the proton release in α-quartz, the well-known crystalline isomer of amorphous silica. When a high concentration of molecular hydrogen (H 2 ) is present, the proton generation can be enhanced by cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Hierarchical constraint means that the energy levels of neutral oxygen vacancies in amorphous SiO 2 are continuously distributed, and the holes are first captured by shallower energy levels and then by deeper energy levels. k c is the rate constant of P b generation due to the H 2 crack on E γ ′ and proton drift to the SiO 2 /Si interface. , Due to the space charge effect of released protons, only part of E γ ′ can be converted to P b at room temperature, as indicated by a proportion of p . Γ [ β , k normalc t ] β ( k normalc t ) β e k c t normalΓ [ β , 0 , k normalc t ] , and normalΓ [ β , 0 , k normalc t ] = 0 k c t x β 1 e x .25em normald x is a generalized incomplete gamma function.…”
Section: Kinetic Model Of Ionization-induced I Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical constraint means that the energy levels of neutral oxygen vacancies in amorphous SiO 2 are continuously distributed, and the holes are first captured by shallower energy levels and then by deeper energy levels. k c is the rate constant of P b generation due to the H 2 crack on E γ ′ and proton drift to the SiO 2 /Si interface. , Due to the space charge effect of released protons, only part of E γ ′ can be converted to P b at room temperature, as indicated by a proportion of p . Γ [ β , k normalc t ] β ( k normalc t ) β e k c t normalΓ [ β , 0 , k normalc t ] , and normalΓ [ β , 0 , k normalc t ] = 0 k c t x β 1 e x .25em normald x is a generalized incomplete gamma function.…”
Section: Kinetic Model Of Ionization-induced I Bmentioning
confidence: 99%
“…In general, ionizing irradiation will cause significant damage to semiconductor devices because electrically active defects are induced in the materials and interfaces. For example, under total ionizing dose (TID) irradiation, the performance of Si electronic devices decays because positively charged oxygen vacancies of puckered configuration, E γ ′ centers, and amphoteric Si dangling bond, P b centers, are induced in SiO 2 and at the SiO 2 /Si interface, respectively. The E γ ′ centers are generated because ionizing-irradiation-induced holes are captured by pre-existing neutral oxygen vacancies in SiO 2 . The P b centers are produced because E γ ′ centers can crack nearby hydrogen molecular (H 2 ) residual from the passivation process and release protons, which under positive bias can drift to the SiO 2 /Si interface , to depassivate pre-existing P b H and finally produce P b centers. As illustrated by the orange quadruple angle stars in Figure , the accumulated P b centers (interface traps) act as recombination centers, , resulting in the growth of base current ( I B ) and the degradation of current gain of bipolar devices . As P b centers are continuously produced under ionizing irradiation, excess I B is expected to grow monotonously with the total dose.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Meanwhile, P b centers are converted from E 0 γ centers through an H 2 -mediated two-step process. First, the generated E 0 γ centers interact with pre-existing H 2 and release protons (H þ ) by breaking the H─H bonds [24,[36][37][38][39][40][41]…”
Section: Defect Dynamics Under a Constant Dose Ratementioning
confidence: 99%
“…Meanwhile, P b centers are converted from E γ centers through an H 2 ‐mediated two‐step process. First, the generated E γ centers interact with pre‐existing H 2 and release protons (H + ) by breaking the HH bonds [ 24,36–41 ] E γ + H 2 * V normalO H * + H + Second, the released protons drift to the SiO 2 /Si interface, react with pre‐existing P b H , and eventually produce P b centers by breaking the SiH bond [ 38,42–46 ] H + + P normalb H * H 2 * + P normalb * Our previous study has indicated that, due to the vibrational energy released from the nonradiative electron capture on E δ , [ 47,48 ] the reacting defects and impurities are in their vibrational excited state (with a superscript of * ) rather than their ground states; [ 11 ] the effective rate constants of the overall forward and backward conversion reactions are k normalf = k 1 + * [ H 2 ] and k normalb = k 1 * [ V normalO H ] k 2 * [ H 2 ] / { k 2 + * [ P normalb H ] } . Here k...…”
Section: Defect Dynamics Under a Constant Dose Ratementioning
confidence: 99%
“…Thus, the contribution to oxide charge accumulation is mainly from puckered configurations. [9] In addition, thermodynamic chargestate transition level depends on the relaxed structures after capturing a hole and then an electron. Uchino studied and summarized the possible relaxation channels of NOVs after hole capture and electron recombination.…”
Section: Introductionmentioning
confidence: 99%